2020
DOI: 10.3390/agronomy10121847
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Soybean (Glycine Max (L.) Merr) Production in Central and South Germany

Abstract: The cultivation area of soybean (Glycine max (L.) Merr) is increasing in Germany as a way to ensure self-sufficiency through its use as feed and food. However, climatic conditions needed for soybean cultivation are not appropriate in all parts of the country. The objective of this study was to determine the influence of solar radiation, temperature, and precipitation on soybean seed productivity and quality in central and south Germany. A multi-factorial field trial was carried out with three replicates at fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
3
27
0
1
Order By: Relevance
“…Mandic et al (2017) reported the soybean seed yield is significantly positively correlated with the rainfall in May, July and August, whereas Bosnjak (2004) recorded a very high correlation between the seed yield and the total rainfall throughout the soybean vegetation period. Also, Sobko et al (2020) recorded a positive correlation between the seed yield and the rainfall over flowering -seed filling and maturing when the soybean plants are especially sensitive to water deficit.…”
Section: Resultsmentioning
confidence: 95%
“…Mandic et al (2017) reported the soybean seed yield is significantly positively correlated with the rainfall in May, July and August, whereas Bosnjak (2004) recorded a very high correlation between the seed yield and the total rainfall throughout the soybean vegetation period. Also, Sobko et al (2020) recorded a positive correlation between the seed yield and the rainfall over flowering -seed filling and maturing when the soybean plants are especially sensitive to water deficit.…”
Section: Resultsmentioning
confidence: 95%
“…The seed development process is determined by both the genetics and the environmental factors including soil fertility, water, temperature, day length, relative humidity, and rainfall [5][6][7][8]. Water deficit condition during plant growth and development leads to reduced plant metabolism and seed development due to reduced photosynthetic rate, assimilate production and translocation to the developing seeds [7,9,10]. It was reported that an increase in temperature (>35 • C) may decrease seed mass because of the higher growth rate and reduced seed filling duration, while low temperatures (<15-17 • C) retard seed growth [5,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Slight variations were found in other studies viz., 16.8−24.9% [ 36 ], 15.7−17.2% [ 42 ], 15.4−22.0% [ 37 ], and 14.2−22.8% [ 38 ]. The highest and lowest oil contents in the genotypes of lowest and highest protein content might be due to a negative correlation between protein and oil content in soybean [ 36 , 38 , 43 ]. The ranges of concentration of palmitic, stearic, oleic, linoleic, and linolenic acids were very close to that found in previous studies of soybean cultivars grown in Korea [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%